2017
DOI: 10.1017/s0029665117000829
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diet-based glycaemic response and glucose regulation on cognition: evidence across the lifespan

Abstract: The brain has a high metabolic rate and its metabolism is almost entirely restricted to oxidative utilisation of glucose. These factors emphasise the extreme dependence of neural tissue on a stable and adequate supply of glucose. Whereas initially it was thought that only glucose deprivation (i.e. under hypoglycaemic conditions) can affect brain function, it has become apparent that low-level fluctuations in central availability can affect neural and consequently, cognitive performance. In the present paper th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 175 publications
(232 reference statements)
1
22
0
Order By: Relevance
“…Previous studies have shown that, similar to CHO-cognition interaction, the effects of CHO ingestion on mood are stronger when participants have to perform difficult cognitive or physical tasks (e.g., Backhouse et al, 2007;Lieberman et al, 2002;Markus, 2007;Owens et al, 1997;Reay et al, 2006). Additionally, methodological choices such as dose, type of CHO and fasting intervals have been shown to affect the magnitude of the CHO facilitation effect and could, theoretically, affect the CHO-mood relationship as well (Riby, 2004;Smith et al, 2011;Sünram-Lea and Owen, 2017). Therefore, one of the predictions of this meta-analysis was that methodological differences across studies would lead to significant heterogeneity in the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that, similar to CHO-cognition interaction, the effects of CHO ingestion on mood are stronger when participants have to perform difficult cognitive or physical tasks (e.g., Backhouse et al, 2007;Lieberman et al, 2002;Markus, 2007;Owens et al, 1997;Reay et al, 2006). Additionally, methodological choices such as dose, type of CHO and fasting intervals have been shown to affect the magnitude of the CHO facilitation effect and could, theoretically, affect the CHO-mood relationship as well (Riby, 2004;Smith et al, 2011;Sünram-Lea and Owen, 2017). Therefore, one of the predictions of this meta-analysis was that methodological differences across studies would lead to significant heterogeneity in the results.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread appeal of sugar-sweetened and energy drinks is associated with the marketing of these products as a way of combating fatigue, increasing energy and promoting a euphoric feeling. As the main ingredient in such drinks is sugar, research has focused on understanding how sugar-sweetened drinks, and carbohydrates (CHOs) in general, might promote cognitive facilitation and emotional wellbeing (for reviews, see Benton, 2002;Benton and Donohoe, 1999;Gibson and Green, 2002;Smith et al, 2011;Sünram-Lea and Owen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding neuroanatomical substrates, those tasks which require greater attentional resources and cognitive control tend to be dependent on frontal regions. It has been suggested that these may be implicated in the glucose facilitation effect (Gailliot & Baumeister, 2007;Sünram-Lea & Owen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that GI affects cognitive performance is based on the knowledge that the brain solely relies on the metabolism of glucose for energy in its non-prolonged fasting state (10) . Overall, there is some evidence that a rapid rise in blood glucose concentration following a high-GI food may improve short-term memory during the first hour following a carbohydratecontaining food, whilst a more sustained glycaemic profile following ingestion of a low-GI food may be beneficial over a longer time frame, for example, throughout the morning (11) . The importance of breakfast on cognitive performance also has some support as there is evidence that breakfast consumption, as opposed to fasting and skipping breakfast, reduces cognitive decline throughout the morning (12)(13)(14) .…”
mentioning
confidence: 99%
“…Although cognitive decline has been found to occur in an induced hypoglycaemic state (15,16) , non-diabetics do not typically experience hypoglycaemia due to the homoeostatic systems in place to prevent it (17) . Indeed, investigators have commented on the need for clarifying the effect of glycaemia on cognition and on whether cognitive function is affected by varying postprandial glycaemic responses to food (11) . Current evidence on this topic has predominantly emanated from studies that lack an appropriate control; consequently, results may be dependent upon qualities of the test foods other than the glycaemic response that they induce.…”
mentioning
confidence: 99%